Comparative Study between Technics of Classic Cesarean and Modern Cesarean - أحمد, إيفلين (Latakia University Journal -Medical Sciences Series, 2021)
The study covered 135 pregnant patients who had primary cesarean section and were going to do their first repeat cesarean by selective indications in Alassad University Hospital in Lattakia in 2010 – 2011 (two years). Patients were divided into two groups depending on the technic of the first cesarean. The first group covered 39 patients who their first cesarean was done by modern method. The second group covered 96 patients who their first cesarean was done by classic method. Comparison between the two groups contained Time for delivery and for all cesarean, Thickness of the lower segment of the uterine (LSCS) and Rate, places and intensity of the adhesions. The results were limitation the time for delivery and the time for all the cesarean by modern method but there were no significant differences in the thickness of (LSCS) and in rate, places and intensity of the adhesions.